KEMAMPUAN ANAK AUTIS DALAM MEMBUAT KALIMAT SEDERHANA DENGAN MENGGUNAKAN KARTU BERGAMBAR - Sri Sadono (Direktorat Guru dan Tenaga Kependidikan Pendidikan Menengah dan Pendidikan Khusus, 2021)
This study aims to determine whether the use of pictorial card media increases students' ability to make simple sentences. This research was arranged by the Classroom Action Research method. The research subjects were Grade IV SLB students, Prof. Dr. Sri Soedewi MS, SH Jambi consisting of 1 student. The procedure of the research is guided by the design of the classroom action research sepiral from Kemmis and McTaggart which includes four stages, namely planning, action, observation and reflection. Data collection uses observation documents, and interviews. After analyzing the research data, the scores obtained by students in cycle I obtained a score of 47, including the medium criteria. After getting the treatment of cycle II action with a picture card game, a score of 68 was included, including high criteria. So it can be concluded that the pictorial card media can improve the ability to make simple sentences.